Comparison of Preemergence Herbicides for Residual Weed Control in Grain Sorghum - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2019)
Herbicides were studied to determine preemergence efficacy in grain sorghum. Velvetleaf and quinoa control did not differ between herbicides late in the season, and no treatment controlled puncturevine more than 81%. The three-way mixture of Callisto, atrazine, and Dual Magnum controlled Palmer amaranth and green foxtail as well as or better than any herbicide tested, whereas most herbicides controlled kochia 88% or more. Compared to the nontreated controls, all herbicides increased sorghum yield 46–146% except Callisto alone at 6 oz/a.
Keywords: residual control